Liquidity risk and hedge fund performance evaluation - Horne, Richard Van (Ryzyko płynności i ocena wyników inwestycyjnych funduszy hedgingowych, 2021)
In this article the author uses two models, a lagged-effects model and a serial correlation model, which identify potential liquidity risk in hedge fund portfolios. From the serial correlation model a liquidity risk factor was developed and added to a multi-factor equilibrium model in order to re-estimate Alpha across a universe of hedge funds. It was found that much of what passes for fund Alpha in a multi-factor risk model lacking a liquidity risk factor is actually a compensation for bearing liquidity risk in the context of a model that includes the innovative liquidity risk factor. This result has implications for both a pre-investment due diligence and a manager selection as well as the postinvestment fund performance evaluation and risk management.
Financial Sciences. Nauki o Finansach, 2021, vol. 26, no. 2, s. 102-125
Keywords: liquidity risk; liquidity factor; alpha ratio; hedge fund performance; ryzyko płynności; czynnik ryzyka płynności; współczynnik alfa; wyniki funduszy hedgingowych